Act of the New Jersey state legislature - New Jersey. Legislature
Act (1822 November 15) incorporating a company for carrying on whale and seal fishing from the port of Perth Amboy, New Jersey, and for banking purposes. Names William S. Pennington, James Parker, and others as commissioners.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Parker, James, -- 1776-1868.; Pennington, William S. -- 1757-1826.; Sealing -- New Jersey -- Perth Amboy; Whaling -- New Jersey -- Perth Amboy